2017
DOI: 10.1007/s11547-017-0759-1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variants of sphenoid sinuses pneumatisation: a CT scan study on a Northern Italian population

Abstract: Sphenoid bone may be affected by different variants of pneumatisation, which have a relevant importance from a clinical and surgical point of view. The description of such variants in different populations may give useful information. However, few articles describe the variability of sphenoid pneumatised structures and none of them focuses on Northern Italian population. Variants of pneumatisation of sphenoid bone were described in a sample of 300 Northern Italian patients who underwent a CT scan. More than fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
0
25
1
3
Order By: Relevance
“…[ 8 9 ] The assessment of variations in pneumatization of SS is essential, yet there is lack of an in-depth study in the Indian population, while the prevalence has been well reported in different ethnic populations. [ 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 9 ] The assessment of variations in pneumatization of SS is essential, yet there is lack of an in-depth study in the Indian population, while the prevalence has been well reported in different ethnic populations. [ 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the study conducted by Surapaneni H et al 20 which had reported the incidence of male candidates affected to be 60% and females 40%. Most of the previous studies performed by vinodhini P 21 , Dua et al 22 , Iseh et al 23 , Gibelli D et al 1 , had showed male preponderance with 66%, 57.5%, 52% and 63% respectively. Surapaneni H et al 20 had demonstrated that the age or gender does not play any significance for causing chronic rhinosinusitis especially with upper respiratory tract infection.…”
Section: Discussionmentioning
confidence: 89%
“…The paranasal sinuses include maxillary, ethmoid, frontal and sphenoid sinuses. 1,2 The main functions of paranasal sinuses include lightening of skull, air humidification and voice resonance. [3][4][5] There are various imaging modalities available for the evaluation of the paranasal sinuses.…”
Section: Introductionmentioning
confidence: 99%
“…Širenje sinusa u okolne delove klinaste kosti je veoma često i istovremeno pokazuje veliku raznolikost, te se klinasti sinus smatra jednom od najvarijabilnijih struktura ljudskog organizma (5). Izučavanje varijacija pneumatizacije klinastog sinusa je od velikog hirurškog i uopšte kliničkog značaja, kako zbog bliskog odnosa sinusa sa krucijalnim neurovaskularnim strukturama, tako i zbog napretka funkcionalne endoskopske hirurgije sinusa.…”
Section: Uvodunclassified
“…Izučavanje varijacija pneumatizacije klinastog sinusa je od velikog hirurškog i uopšte kliničkog značaja, kako zbog bliskog odnosa sinusa sa krucijalnim neurovaskularnim strukturama, tako i zbog napretka funkcionalne endoskopske hirurgije sinusa. Klinasti sinus predstavlja put za endoskopski transsfenoidalni pristup hipofizi, te je to takođe polje u kome poznavanje ekstenzija klinastog sinusa nalazi svoju primenu (4)(5)(6). Moguće je i da pneumatizovane strukture doprinose povećanju rizika za pojavu hroničnog sinuzitisa, tokom koga okolni sudovi i živci mogu biti izloženi oboljenjima kao što su neuralgija trigeminalnog nerva, problem sa vidom i slično (5).…”
Section: Uvodunclassified